Smart logistic for sustainable cities - Setiawan, Christopher Hendra; Santoso, Amelia; Parung, Joniarto (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The United Nations has agreed on sustainable cities to be one of a series of sustainable development goals (SDGs) as the eleventh goal. This shows the seriousness of the world government in viewing the role of cities to participate in building the concept of sustainability. However, on the other hand, the phenomenon of urbanization continues to increase from year to year. The increase in urbanization is followed by an increase in the number of motorized vehicles, including logistics activities in it. The increase in logistics and transportation activities has a negative impact on air quality in urban areas with its CO2 emissions. Poor air quality will certainly hamper a city's efforts in achieving the concept of sustainability or sustainable cities. Thus, solutions to improve logistics activities are needed in an effort to achieve the sustainability of a city. In today's digital era, the role of technology is enormous including in the field of logistics, by integrating technology with logistics activities, more optimal solutions related to efficiency and so on will be more easily recorded. This integration concept is known as smart logistics. This research presents the results of a review of various literatures to define the concept of sustainable cities, the concept of smart logistics, and what logistics solutions have been studied before and how these solutions can answer the challenges posed in the development of the concept of sustainable cities